Effectiveness of Correctional Programs With Ethnically Diverse Offenders: A Meta-Analytic Study. (February 2014) - Usher, Amelia M.; Stewart, Lynn A.
Numerous studies have examined the effects of cognitive-behavioural therapy (CBT) on criminal recidivism, and several meta-analyses have confirmed the overall effectiveness of this approach. Few studies, however, have examined the efficacy of these programs specifically with adult offenders from diverse ethnic backgrounds. The present research uses meta-analytic techniques to examine the outcomes for Canadian federal offenders participating in correctional programs according to self-identified ethnic group (Caucasian, Aboriginal, Black, and Other). Correctional programs within the Correctional Service of Canada adhere to the Risk, Need, Responsivity principles outlined in the effective correctional literature. Within-group analyses compared offenders from the same ethnic background who participated in correctional programs with a nontreatment comparison group. Odds ratios ranged from 1.36 to 1.76, indicating significant reductions in recidivism for offenders participating in correctional programs, regardless of ethnic status. Furthermore, the difference in effect size magnitude between ethnic groups was nonsignificant suggesting offenders from a wide variety of ethnic backgrounds can benefit from correctional programs rigorously developed and implemented using a CBT framework.